A search for new resonances in multiple final states with a high transverse momentum Z boson in s $$ \sqrt{s} $$ = 13 TeV pp collisions with the ATLAS detector. (Tufts University. Tisch Library., 2023)
Keywords : Beyond Standard Model, Hadron-Hadron Scattering, Particle and Resonance Production.; Springer Open.